Teaching writing in the disciplines: Student perspectives on learning genre - Goldschmidt, Mary (Teaching and Learning Inquiry, 2014)
Writing in the Disciplines curricula can both challenge and reinforce assumptions that writing is a general skill that students will already have learned prior to doing the specialized writing in their chosen field of study. Rhetorical genre studies, however, tends to emphasize the situated nature of writing expertise, and thus supports the exploration of more sustained and varied forms of writing instruction in higher education. This article reports on a qualitative study that gave priority to a rich source of pedagogical insight: student writers themselves. In-depth interviews and surveys were used to examine the pedagogical practices and curricular experiences identified by students as being most helpful in developing undergraduate expertise in their discipline’s research genre. These student-centered descriptions of successful genre learning point the way toward curricular and instructional models that emphasize the intellectual, affective, and relational nature of writing.